2021
DOI: 10.1101/2021.01.26.21250498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Addiction Risk Factor: A Unitary Genetic Vulnerability Characterizes Substance Use Disorders and Their Associations with Common Correlates

Abstract: BackgroundSubstance use disorders (SUDs) commonly co-occur with one another and with other psychiatric disorders. They share common features including high impulsivity, negative affect, and lower executive function. We estimate the shared genetic architecture across distinct SUDs, its independence from genetic liability to substance use, and its relation to genetic liability to impulsivity, negative affect, and executive function as well as non-substance psychopathology.MethodsWe tested whether a common geneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Consistent with recent reports demonstrating broad levels of pleiotropy amongst psychiatric disorders (Lee et al, 2019), including substance use disorders (Hatoum et al, 2021), we found that 22 of the 55 top convergent SNPs and 3 of the 8 divergent SNPs showed at least nominal significance across one or more of the six psychiatric disorders and substance use traits that we assessed. Depression showed the greatest extent of overlap with the convergent SNPs, with 10 of the 55 convergent SNPs having p < 0.0009 in the depression GWAS and only one of those exerting a different direction of effect relative to AUD and SCZ.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with recent reports demonstrating broad levels of pleiotropy amongst psychiatric disorders (Lee et al, 2019), including substance use disorders (Hatoum et al, 2021), we found that 22 of the 55 top convergent SNPs and 3 of the 8 divergent SNPs showed at least nominal significance across one or more of the six psychiatric disorders and substance use traits that we assessed. Depression showed the greatest extent of overlap with the convergent SNPs, with 10 of the 55 convergent SNPs having p < 0.0009 in the depression GWAS and only one of those exerting a different direction of effect relative to AUD and SCZ.…”
Section: Discussionsupporting
confidence: 91%
“…substance-specific genetic influences, reporting evidence to suggest the presence of a common unitary addiction factor that can account for risk across SUDs, in addition to substance-specific influences (46). Larger-scale studies of OUD will be needed to advance OUD genetic discovery and parse genomic influences specific to OUD from those underlying risk for SUDs more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Summary statistics for the SUDs came from four independent studies, which to our knowledge are the largest available GWAS for each phenotype. We chose to use these phenotypes specifically as their contributions to a common genetic addictions factor are well-studied (Hatoum et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity amongst SUDs and their distinct genetic relationships with other dimensions of mental health are becoming increasingly better understood (Abdellaoui et al, 2021; Hatoum et al, 2021). Recently, Hatoum et al (preprint; 2021) proposed a unidimensional factor for characterizing substance use disorders, specifically problematic alcohol use (PAU), cannabis use disorder (CUD), opioid use disorder (OUD) and problematic tobacco use.…”
Section: Introductionmentioning
confidence: 99%